Assessing the Role of Behavioral Activation System (Bas)/Behavioral Inhibition System (Bis) and Self-Esteem in Online Trolling Behavior (Bioresearch Communications, 2026)
Background: Online trolling is a provocative and obnoxious conduct that takes place online and is associated with participating in anonymous actions making other people feel unpleasant. The two fundamental motivational systems accountable for regulating human behavior, Behavioral Inhibition System (BIS)/Behavioral Activation System (BAS), might contribute to the understanding of this kind of behavior. Objectives: In this cross-sectional study, we examined the links between the BIS/ BAS, internet trolling, and self-esteem among adult online multiplayer gamers in Bangladesh. Methods: Global Assessment of Internet Trolling (GAIT) scale, the BIS/BAS scales, and Rosenberg self-esteem scale were used to measure study variables. These scales were administered to 131 adult online multiplayer gamers (107 male and 24 female) using snowball sampling approach. Their age range was 18- 31 years (M = 21.96, SD = 3.20). Results: After age, gender and socio-economic status were controlled for, BIS, and BAS (reward responsivity, drive, and fun seeking) were examined for their predictive utility of online trolling behavior. Results revealed that self-esteem is not substantially connected with internet trolling behavior, and that it is predicted by low BIS and high fun-seeking tendency – one of the BAS subscales. Conclusion: These results imply that inherent temperamental tendencies may make people more likely to annoy others online for personal gain and enjoyment.Bioresearch Commu. 12(1): 1933-1940, 2026 (January)